2017
DOI: 10.1038/s41598-017-04589-6
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the cellulose-producing strain Komagataeibacter nataicola RZS01

Abstract: Komagataeibacter nataicola is an acetic acid bacterium (AAB) that can produce abundant bacterial cellulose and tolerate high concentrations of acetic acid. To globally understand its fermentation characteristics, we present a high-quality complete genome sequence of K. nataicola RZS01. The genome consists of a 3,485,191-bp chromosome and 6 plasmids, which encode 3,514 proteins and bear three cellulose synthase operons. Phylogenetic analysis at the genome level provides convincing evidence of the evolutionary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Conjugative plasmid DNA transfer, in cellulose‐producing and cellulose nonproducing derivatives of K. xylinus ATCC 10245 (in the original paper: Acetobacter xylinum ATCC 10245) strain, has been shown in pioneering studies of Jackson, Vinatzer, Arnold, Dorus, and Murillo (). The complete genomic sequences of Komagataeibacter strains ( K. xylinus E25 (Kubiak et al., ), K. medellinensis NBRC 3288 (Ogino et al., ), and the two strains deposited during the time of preparation of this manuscript— K. nataicola RZS01—(Zhang et al., ) and K. europaeus SRCM 101446; unpublished) have shown the presence of five, seven, six, and three plasmids in these strains, accordingly. In case of the three in‐house strains sequenced here, the results of mapping of sequencing reads to the K. xylinus E25 genome suggested the presence of at least two small plasmids (~5 kbp and ~2 kbp) in K. xylinus E26 and K. xylinus BCRC 12334 strains (Figure c).…”
Section: Resultsmentioning
confidence: 95%
“…Conjugative plasmid DNA transfer, in cellulose‐producing and cellulose nonproducing derivatives of K. xylinus ATCC 10245 (in the original paper: Acetobacter xylinum ATCC 10245) strain, has been shown in pioneering studies of Jackson, Vinatzer, Arnold, Dorus, and Murillo (). The complete genomic sequences of Komagataeibacter strains ( K. xylinus E25 (Kubiak et al., ), K. medellinensis NBRC 3288 (Ogino et al., ), and the two strains deposited during the time of preparation of this manuscript— K. nataicola RZS01—(Zhang et al., ) and K. europaeus SRCM 101446; unpublished) have shown the presence of five, seven, six, and three plasmids in these strains, accordingly. In case of the three in‐house strains sequenced here, the results of mapping of sequencing reads to the K. xylinus E25 genome suggested the presence of at least two small plasmids (~5 kbp and ~2 kbp) in K. xylinus E26 and K. xylinus BCRC 12334 strains (Figure c).…”
Section: Resultsmentioning
confidence: 95%
“…Also, this phylogenetic analysis recapitulated phylogenetic difference between Komagataeibacter species and Gluconacetobacter species (the former genus name of K. xylinus DSM 2325) as species from both genera were not clustered together. Closer examination of K. xylinus DSM 2325 with the other six Komagataeibacter species, all with complete genome sequences, showed that K. xylinus DSM 2325 appeared to have the genome contents most similar to Komagataeibacter nataicola RZS01 rather than another same species K. xylinus E25 or K. xylinus CGMCC 2955 (Figure b); the six species were Komagataeibacter medellinensis NBRC 3288 (Ogino et al, ), K. nataicola RZS01 (Zhang et al, ), K. xylinus E25 (Kubiak et al, ), Komagataeibacter hansenii ATCC 23769 (Iyer, Geib, Catchmark, Kao, & Tien, ), K. xylinus CGMCC 2955 (Liu et al, ), and Komagataeibacter europaeus SRCM101446 (not published). It should be noted that 29 metabolic genes were found to be exclusively present in K. xylinus DSM 2325, and absent in K. nataicola RZS01 (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose metabolism is the main energy source of ATP production. Interestingly, in most of the CNF-producing bacteria, glucose is metabolized through the oxidative pentose phosphate pathway and not the Embden-Meyerhof-Parnas (EMP) pathway, because of a lack of the pfkA gene, which is encoded with phosphofructokinase (24)(25)(26). The absence of the pfkA gene is a very well-known genotypic feature of the Komagataeibacter species, but the gene expression effect has not been studied well until now.…”
Section: Significancementioning
confidence: 99%